Local and standardized strategies: A content analysis of newspaper food and beverage advertising in Jamaica. (June 2020) - Ahn, Regina Jihea; Nelson, Michelle R.; Ferguson, Gail M.
Globalization has led to changes in diets and advertising linked to audience preferences. This study examines local and global brand food and beverage advertising in Jamaican newspapers. Content analysis of 440 advertisements revealed the predominance of global fast-food brands, often including soda. Healthier foods were found in one in 10 ads. Information cues included taste, quality, and price, yet 14% of ads featured only a product image/logo. Advertisements reflected standardized and local strategies.